Ultraviolet B Exposure Does Not Influence the Expression of YAP mRNA in Human Epidermal Keratinocytes—Preliminary Study - Igor Aleksander Bednarski; Izabela Dróżdż; Magdalena Ciążyńska; Karolina Wódz; Joanna Narbutt; Aleksandra Lesiak (Biomedicines)
Background: The causal relationship between exposure to ultraviolet radiation and the development of skin cancers requires constant research for possible orchestrating mechanisms. In recent years, the Hippo pathway, along with its effector protein YAP, became implicated in cutaneous carcinogenesis; however, Hippo pathway regulation by ultraviolet radiation has not been described thoroughly. In order to address this issue, we focused on how different doses of ultraviolet B affect Hippo signaling pathway components and its upstream regulators, JNK1/2 and ABL1, in human keratinocytes. Additionally, we decided to determine how silencing of YAP influences Hippo pathway component expression. Methods: Primary epidermal keratinocytes were irradiated using UVB lamps with increasing doses of ultraviolet B radiation (including 311 nm UVB). Real-time PCR was used to determine the mRNA levels of each investigated gene. The experiment was then performed after YAP silencing using siRNA transfection. Additionally, we determined the mRNA expression of Hippo pathway components in an A431 cSCC cell line. Results: We observed that YAP mRNA expression in the A431 cell line was insignificant in comparison to control, while in the case of LATS1/2, a significant increase was noted. UVB irradiation did not change the levels of YAP mRNA expression in human epidermal keratinocytes. LATS1, LATS2, ABL1 and MAP4K4 mRNA expression was significantly upregulated after UVB irradiation in non-YAP-silenced keratinocytes in a dose-dependent manner, while after YAP silencing, only LATS2 and ABL1 showed significant mRNA upregulation. The 311 nm UVB irradiation resulted in significant, dose-dependent mRNA upregulation in non-YAP-silenced keratinocytes for LATS1, ABL1 and MAP4K4. After YAP silencing, a significant change in mRNA expression was present only in the case of ABL1. Conclusions: YAP mRNA expression does not significantly increase after exposure to UVB; however, it upregulates the expression of its proven (LATS1/2, JNK1/2) regulators, suggesting that in real-life settings, UV-induced dysregulation of the Hippo pathway may not be limited to YAP.